The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
1999
DOI: 10.1590/1809-43921999293500
|View full text |Cite
|
Sign up to set email alerts
|

Biodisponibilidade de vitamina a da pupunha (Bactris gasipaes Kunth) em Ratos

Abstract: RESUMO -Considerando a magnitude da hipovitaminose A como problema de saúde pública no mundo e a disponibilidade de frutos ricos em pró-vitamina A, como a pupunha (Bactris gasipaes Kunth) na região Amazônica, determinou-se a biodisponibilidade de vitamina A da mesma em ratos, utilizando o método preventivo. Os resultados indicaram ser a pupunha uma fonte de vitamina A altamente biodisponível, com eficiência relativa de 250,8% quando comparado com o grupo controle (100%).Palavras-chave: vitamina A; pupunha; bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
2

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 6 publications
(3 reference statements)
0
4
0
2
Order By: Relevance
“…In previous reports, Yuyama et al evaluated the bioavailability of carotenoids from other two palm fruits, buriti (Mauritia flexuosa L.) and pupunha (Bactris gasipaes Kunth), using liver retinol accumulation in rats. The authors also found higher β-carotene bioavailability in the groups fed diets supplemented with buriti and pupunha flours in relation to the retinyl palmitate, the respective control group (33,34). These results suggest that these Brazilian palm fruits may be a good source of β-carotene and vitamin A for rats; however, the ability of this model to predict bioavailability in a healthy human population needs to be verified.…”
Section: Resultsmentioning
confidence: 95%
“…In previous reports, Yuyama et al evaluated the bioavailability of carotenoids from other two palm fruits, buriti (Mauritia flexuosa L.) and pupunha (Bactris gasipaes Kunth), using liver retinol accumulation in rats. The authors also found higher β-carotene bioavailability in the groups fed diets supplemented with buriti and pupunha flours in relation to the retinyl palmitate, the respective control group (33,34). These results suggest that these Brazilian palm fruits may be a good source of β-carotene and vitamin A for rats; however, the ability of this model to predict bioavailability in a healthy human population needs to be verified.…”
Section: Resultsmentioning
confidence: 95%
“…Regarding vitamins (fat and water soluble), peach palm fruit is seen as a good source of vitamins A, B, and C, in addition to the mesocarp being rich in α-tocopherol, similar to other species in the Amazon region [ 107 , 114 , 115 ]. Yuyama et al [ 115 ] evaluated the bioavailability of vitamin A from the peach palm using the preventive method in rats.…”
Section: Peach Palm Products: Diversity In Consumption Chemical Compo...mentioning
confidence: 99%
“…Exclusive olive oil consumption has been reported to be directly linked to lower risk of coronary artery disease [1]. Plants from Amazonian Region have a diversity of fruits like açaí [2], bacaba [3][4][5], buriti [6][7][8], pupunha [3,9,10] that can be used as source of functional oils due to their high contents of phenolic compounds, as well as lipossoluble vitamins and unsaturated fatty acids. Many of these fruits present pulp and seeds rich in oils [1] containing saturated and unsaturated fatty acids with nutritional value that may comparable to ingredients of Mediterranean diet.…”
Section: Introductionmentioning
confidence: 99%